Using suitable identity, find (x − 2y + 3)^2 - (x + 2y − 3)^2
Answers
Answered by
0
Step-by-step explanation:
On simplification , we get
(x−2y+3)
2
+(x+2y−3)
2
⟹2(x)
2
+8y
2
+2(3)
2
+2.(x)(−2y)+2.(−2y)(3)+2.(x)(3)+2.(x)(2y)+2.(2y)(−3)+2.(−3)(x)
⟹2x
2
+8y
2
+18−24y
Answered by
0
Answer:
On simplification , we get
(x−2y+3)2+(x+2y−3)2
⟹2(x)2+8y2+2(3)2+2.(x)(−2y)+2.(−2y)(3)+2.(x)(3)+2.(x)(2y)+2.(2y)(−3)+2.(−3)(x)
⟹2x2+8y2+18−24y
Similar questions
Biology,
23 hours ago
Math,
23 hours ago
Social Sciences,
23 hours ago
Math,
1 day ago
Math,
1 day ago
Social Sciences,
8 months ago
Physics,
8 months ago
English,
8 months ago